2015
DOI: 10.5152/tjg.2015.6123
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of 35 children with abdominal tuberculosis

Abstract: Background/Aims: To contribute to the diagnosis and treatment of pediatric abdominal tuberculosis cases by assessing the clinical, laboratory, and radiological features of patients who presented at our clinic and were diagnosed with abdominal tuberculosis. Materials and Methods: Clinical, laboratory, and radiological features were reviewed retrospectively for 35 patients diagnosed with abdominal tuberculosis and followed up at the Pediatric Infectious Diseases Clinic between January 1987 and August 2012. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 25 publications
1
6
0
8
Order By: Relevance
“…Most common clinical signs and symptoms are fever, weight loss, abdominal pain, abdominal swelling, hepatomegaly, diarrhea and constipation, fatigue and malaise (3,10,11,25). The most common symptoms reported in various studies were fever (73% -75%) (12,26), weight loss (46.9% -81%) (12,27), fatigue (81%) (27), and abdominal pain (51.2% -93%) (12,24,28,29). In agreement with the literature the clinical symptoms of the study patients were similarly nonspecific; the most common of which was abdominal pain observed in all patients, followed by fever (50%) and abdominal distension (25%).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Most common clinical signs and symptoms are fever, weight loss, abdominal pain, abdominal swelling, hepatomegaly, diarrhea and constipation, fatigue and malaise (3,10,11,25). The most common symptoms reported in various studies were fever (73% -75%) (12,26), weight loss (46.9% -81%) (12,27), fatigue (81%) (27), and abdominal pain (51.2% -93%) (12,24,28,29). In agreement with the literature the clinical symptoms of the study patients were similarly nonspecific; the most common of which was abdominal pain observed in all patients, followed by fever (50%) and abdominal distension (25%).…”
Section: Discussionsupporting
confidence: 85%
“…The frequency of abdominal TB is also rare in Turkey; in the present study there were only eight children in a four-year period which is similar to a previous report where Dinler et al (10) followed nine children in a five year period in the Black sea region of Turkey. Kilic et al (24) reported 35 children diagnosed with abdominal TB in a fifteen year period. The mean age of our study population was 13.6 ± 2.8 (range, 7 -16) years, which is in compliance with the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Viral gastroenteritis generally does not increase the thickness of the bowel wall; however enlarged lymph nodes and free fluid may be present [41]. Tuberculosis may also present with bowel wall thickening along with hepatosplenomegaly, omental thickening, and typical internal echoes and septations within ascites [54]. Parasites can be revealed by US as mobile, tubular hypoechoic structures with hyperechoic rim in Ascariasis infection, with parallel echogenic lines representing digestive system [41].…”
Section: Ileum Involvementmentioning
confidence: 99%
“…Viral gastroenteritis usually does not demonstrate bowel wall thickening, though ascites and enlarged nodes may be present [67] . Intestinal tuberculosis may show bowel wall thickening, typically with associated hepatosplenomegaly and omental thickening; findings may mimic Crohn disease [68,69] . Typhlitis, or inflammation of the cecum, is more frequently seen in immunocompromised patients and is characterized by marked thickening and hypervascularity; increased thickness of the wall may correlate with a worse prognosis [70,71] .…”
Section: A B C Dmentioning
confidence: 99%